Analyzing the impact of viral marketing and brand awareness on crocs’ purchase intentions among millennials and gen z - Zakiyyah, Nada Hasya; Prayitno, Sentot Basuki (Jurnal Mantik, 2025)
This study aims to determine how Crocs' viral marketing strategy influences consumer behavior among Millennials and Gen Z. This study explores how Crocs' viral marketing and brand awareness influence purchase intention among Millennials and Gen Z. With the highest penetration rate in 2023, Jakarta, Bogor, Depok, Tangerang, and Bekasi were selected as the research locations. To collect data, the author conducted an anonymous survey via Google Forms, using the Likert Scale for measurement. A total of 197 respondents participated in the survey. The data were analyzed using multiple linear regression with IBM SPSS 26 and SmartPLS 4.0 software. Although the findings revealed overlapping variations that led to the merging of independent variables into one construct for hypothesis testing, the results showed that viral marketing and brand awareness had a positive impact on Crocs' purchase intention in the Jabodetabek area. This suggests that Crocs' digital marketing efforts have successfully engaged Millennials and Gen Z, encouraging them to consider purchasing Crocs products. The positive impact of this marketing strategy highlights how targeting specific consumer segments through a tailored approach can be effective. The results underscore the importance of understanding and leveraging digital marketing to connect with younger consumers. For businesses looking to engage Millennials and Gen Z, investing in viral marketing and building strong brand awareness is critical. This study provides valuable insights for businesses and researchers, demonstrating the effectiveness of digital marketing in influencing purchase intent among younger consumers. By focusing on digital and viral marketing strategies, companies can better connect with this influential consumer group and drive future growth